(untitled) (Bulletin KNOB, 2005)
Economic activities strongly increased in the Dutch East Indies after the abolition of the system of forced farming in 1870. The strong increase in the number of European inhabitants initiated a veritable building boom at the end of the 19th century. The towns, especially those on Java, experienced a period of explosive growth. In order to meet the increasing demand for buildings, more private architects settled in the Dutch East Indies in the first decades of the 20th century. In the first half of the twenties a subject of heated discussion was what modern Dutch East Indian architecture ought to look like. There were two opposed parties, each with its own views on the Eurasian architectural style yet to be developed. The party oriented towards Europe, represented by prof. ir. Charles Prosper Wolff Schoemaker, was looking for an architecture based on modern European architecture, but closely related to the tropical surroundings. The other party aimed at finding a basis in the architectural history of the Indonesian archipelago, improved with the technical achievements of western architecture. The major representative of this ’Vernacular’ group was Henri Maclaine Pont. With the establishment and construction of the Dutch East Indian Institute of Technology in Bandoeng in 1918-1920 of architect Maclaine Pont (ill. 3) and also of the building for the Department of Government Companies of architect Gerber (ill. 14) (popularly called Gedung Sateh, after the decoration on the roof) from the same period, the design of Dutch East Indian architecture was called into question. Wolff Schoemaker rejected the design of these buildings because of the use of incorrectly interpreted decoration and the fact that a Sumatran building style had been transferred to Java. The dispute between Wolff Schoemaker and Maclaine Pont came to a head in the pendopo as the most characteristic Javanese Building form (ill. 8). They particularly disagreed on the structural advantages of the pendopo, scornfully called ’the degenerate Javanese, utterly weakened art of timber construction’. Maclaine Pont, however, praised the construction because of its resistance against the frequently occurring earthquakes on Java. In practice the differences between the parties were not so fundamental as the sometimes fierce discussion leads one to suspect and this can easily be seen in the buildings of these architects. From the point of view of the then current western style of building Wolff Schoemaker and Maclaine Pont developed an architecture that was physically adjusted to the tropics. The discussion on architecture very soon lost its momentum; although the discussants did not come any closer, the discussion did strengthen the confidence of the Dutch East Indian architects in their own capabilities. The Institute of Technology, the public theatre Sobokarti of Thomas Karsten (ill. 9), Gedung Sateh and the Mosque of Wolff Schoemaker (ill. 11) are important landmarks in the search for an individual Dutch East Indian architectural style. Designed from various points of view, these buildings fit into the Framptomian concept of Critical Regionalism. However, the approach taken in order to bridge the different cultures came to a dead end when the Second World War began to cast its shadow. The Dutch East Indian architecture in statu nascendi was outrun by the international political developments. After the war the situation in the Dutch East Indies had changed completely. The first president of Indonesia, ir. Soekarno, a pupil of prof. Wolff Schoemaker, was increasingly leaving his mark on architecture and urban design. He did not look for the future of Indonesian architecture in its own history, to him that was a romantic ideal from before the war. Architecture should express that the new Indonesia wished to be a modern, national, unified state. In Soekarno’s opinion the native building styles were not only old-fashioned but also emphasized the great diversity of cultures within the country. Consequently, a discussion on a style in which that variety would be stressed was no longer relevant.